(untitled) (Journal of the College of Basic Education, 2022)
The research aims to identify effect of exercises and kinetic formations with apersonalized tool on creativity kinetic for second stage students -Department of Physical Education and Sports Sciences - Faculty of Basic Education- Mustansiriya University. The researchers used the experimental approach to suit the purpose and hypotheses of the research which is based on the design of two groups (control - experimental), The research community included students of the second stage Department of Physical Education and Sports Sciences - Faculty of Basic Education - University of Mustansiriya has been conducted homogeneity of the control and experimental groups. Data collection methods were used which facilitates the achievement of the goal of research, the most important results indicated that the proposed program has a positive impact on the factors of motor creativity under study by the students of the experimental group there were statistically significant differences in favor of the Post-test of the experimental group, The researchers recommend the need to adopt the exercises formations in the mobility curriculum as well as emphasizing the importance of developing the factors of motor creativity because of its positive impact on performance in the rhythmic gymnastic.